Multi‐institutional investigation of the prognostic value of lymph nodel yield in advanced‐stage oral cavity squamous cell carcinoma. Issue 10 (13th January 2014) - Jaber, James J.; Zender, Chad A.; Mehta, Vikas; Davis, Kara; Ferris, Robert L.; Lavertu, Pierre; Rezaee, Rod; Feustel, Paul J.; Johnson, Jonas T.
Abstract Background Although existing literature provides surgical recommendations for treating occult disease (cN0) in early‐stage oral cavity squamous cell carcinoma (SCC), a focus on late‐stage oral cavity SCC is less pervasive. Methods The medical records of 162 patients with late‐stage oral cavity SCC pN0 who underwent primary neck dissections were reviewed. Lymph node yield as a prognosticator was examined. Results Despite being staged pN0, patients that had a higher lymph node yield had an improved regional/distant control rates, disease‐free survival (DFS), disease‐specific survival (DSS), and overall survival (OS). Lymph node yield consistently outperformed all other standard variables as being the single best prognostic factor with a tight risk ratio range (RR = 0.95–0.98) even when correcting for the number of lymph nodes examined. Conclusion The results of this study showed that lower regional recurrence rates and improved survival outcomes were seen as lymph node yield increased for advanced T classification oral cavity SCC pN0. This suggests that increasing lymph node yield with an extended cervical lymphadenectomy may result in lower recurrence rates and improved survival outcomes for this advanced stage group. © 2014 Wiley Periodicals, Inc. Head Neck, 36: 1446–1452, 2014